Finite element analysis of anterior cruciate ligament reconstruction techniques: A comparison of the mechanical properties of all-inside fixation and traditional fixation - Chen, Xiaodong; Xue, Changguo; Li, Kuanxin; Mu, Kecheng; Yao, Cheng; Wang, Zhiyan; Chen, Hongzhi; Zhang, Jun (Frontiers in Bioengineering and Biotechnology, 2024)
Objective The main purpose of this study was to explore the mechanical properties of the anterior cruciate ligament and its attachments following reconstruction with the all-inside technique after anterior cruciate ligament injury. Methods Knee joint computed tomography data were collected from healthy volunteers, and knee joint models were created using Mimics software. A normal knee joint model, an all-inside reconstructed anterior cruciate ligament model, and a traditional reconstructed anterior cruciate ligament model were established. A tensile force of 134 N and a bending moment of 5 N/m were applied at the anterior aspect of the proximal tibia in these three models. The knee joint was subjected to external rotation, internal rotation, varus, valgus, flexion, and extension under this bending moment. The magnitude and distribution of stress on the ligament or graft and the magnitude and distribution of stress on the graft attachments were observed under different loading conditions. Results Under different external forces, the maximum stress on the ligament in the normal model fluctuated from 1.949 to 18.302 MPa, with an uncertain distribution of maximum stress. The maximum stress on the graft in the all-inside reconstructed anterior cruciate ligament model fluctuated from 0.705 to 3.465 MPa and was mainly distributed at the junction of the graft and the tibial footprint. In the traditional reconstructed anterior cruciate ligament model, the maximum stress on the graft fluctuated from 5.012 to 59.269 MPa and was primarily distributed at the junction of the interference screw and the graft. The concentration of stress on the loop and plate in the all-inside reconstructed anterior cruciate ligament model fluctuated from 70.461 to 346.363 MPa, with maximum stress distributed at the junction of the loop and the tibial surface. The maximum stress on the interference screw in the traditional reconstructed anterior cruciate ligament model fluctuated from 10.184 to 92.298 MPa, with maximum stress primarily distributed at the end of the interference screw. Conclusion Under different external forces, the graft used in all-inside anterior cruciate ligament reconstruction is subjected to fewer external forces than that used in traditional anterior cruciate ligament reconstruction, which may indicate a relatively stable mechanical environment. The strength of the loop and plate can theoretically tolerate daily knee joint movements of patients without injury.